Nanobiostimulants Emerging Strategies for Agricultural Sustainability - Singh, Vandana; Bhat, Rouf Ahmad; Dar, Gowhar Hamid; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
The book describes how nanobiostimulants, which are nanoscale materials that can enhance plant growth and productivity, have the potential to revolutionize sustainable agriculture practices. The book covers a wide range of topics, including the properties and functions of nanobiostimulants, the mechanisms behind their effects on plant growth, and the potential risks associated with their use. It also discusses how nanobiostimulants can be used to improve soil health and nutrient uptake, enhance plant resistance to environmental stresses, and increase crop yields. Overall, the book provides a comprehensive overview of the emerging field of nanobiostimulants and its potential applications in sustainable agriculture. It will be of interest to researchers, students, and professionals in the fields of agriculture, nanotechnology, and environmental science.
Chapter 1: Introduction to Nanobiostimulants in Sustainable Agriculture -- Chapter 2: Nanofertilizers: A new frontier in agriculture -- Chapter 3: Green Synthesis of Nanobiostimulants and their applications -- Chapter 4: Valorisation of biomass to bio stimulants -- Chapter 5: Nanobiostimulants and Plant-Microbe Interactions -- Chapter 6: Nanobiostimulants for Enhancing Plant Growth and Yield -- Chapter 7: Nanobiostimulants: Precision tools for harnessing soil microbes and elevating agricultural productivity -- Chapter 8: Nanobiostimulants for Enhancing Plant Stress Tolerance -- Chapter 9: Harnessing Nano Bio-Stimulants for Sustainable Agriculture: Unraveling Plant-Microbe Synergies -- Chapter 10: Nanobiochar - A Nanostimulant for Enhancing Soil Quality and Sustainability -- Chapter 11: Nanobiostimulants : the nanoscopic bioeffecttors in Seed germination and Plant Establishment -- Chapter 12: Nanobiostimulants and Plant Secondary Metabolites -- Chapter 13: Nanobiostimulants and Sustainable Crop Production -- Chapter 14: The Role of Nanobiostimulants in Modulating Plant-Microbe Symbioses for Enhanced Crop Productivity -- Chapter 15: Nanobiostimulants and Climate Change Adaptation in Agriculture -- Chapter 16: Nanobiostimulants and Precision Agriculture: A Data-Driven Approach to Farming and Market Dynamics -- Chapter 17: Commercialization and Market Potential of Nanobiostimulants -- Chapter 18: Environmental Impacts of Nanobiostimulants -- Chapter 19: The world of nanobiostimulants impacting the environment -- Chapter 20: Nano-biostimulants For Improving Plant Roots Regulations and Nutrient Uptake -- Chapter 21: Ecological Perspectives on Nano-Biostimulant Applications in Agriculture.
Keywords: Environmental engineering; Biotechnology; Bioremediation; Agriculture; Nanobiotechnology; Environmental Engineering/Biotechnology.; Agriculture; Nanobiotechnology